2014
DOI: 10.2147/vhrm.s61019
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid profile and its association with hypertension in Bangladesh

Abstract: BackgroundHypertension and dyslipidemia are major risk factors for cardiovascular disease, accounting for the highest morbidity and mortality among the Bangladeshi population. The objective of this study was to determine the association between serum lipid profiles in hypertensive patients with normotensive control subjects in Bangladesh.MethodsA cross-sectional study was carried out among 234 participants including 159 hypertensive patients and 75 normotensive controls from January to December 2012 in the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…The urban–rural differences in dyslipidemias are consistent with distribution of other variables, such as obesity or diabetes. The validity of our findings is supported by the fact that being female, higher BMI and WHR, diabetes and hypertension were also positively significantly associated with dyslipidemia, similarly to other published studies [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…The urban–rural differences in dyslipidemias are consistent with distribution of other variables, such as obesity or diabetes. The validity of our findings is supported by the fact that being female, higher BMI and WHR, diabetes and hypertension were also positively significantly associated with dyslipidemia, similarly to other published studies [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, in a previous study we showed that hypertensive patients in Bangladesh have a close association with dyslipidemia. 45 Future advanced studies will provide better pathophysiology and genetics basis of hypertension in Bangladesh. Finally, we did not collect data on medication use and adherence, which could have provided better clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…Both BMI and WHR are predictors of CVD and mortality [ 23 ]. A study in Bangladesh showed an association between hypertension and dyslipidemia [ 24 ]. In our study young AMI patients had higher dyslipidemia and lower hypertension than older patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the younger group reported to consume significantly higher frequency of rice and beef and significantly lower frequency of fruits and vegetables compared to the older group. Previous studies have shown that unhealthy diet rich in carbohydrate and low in fruits and vegetables are a major risk factor for CVD [ 24 , 29 , 30 ]. Dietary results are difficult to compare due to differences in study design and variations of food habits in different countries.…”
Section: Discussionmentioning
confidence: 99%